Divergent seasonal responses of above- and below-ground to environmental factors in alpine grassland - Qin, Xiaojing; Nie, Xiaojun; Wang, Xiaodan; Hong, Jiangtao; Yan, Yan (Frontiers in Plant Science, 2023)
Abstract: Under current global warming, the relationship between season changes of plant and environmental factors is focused in high-elevation and latitude regions. Due to the synchronous of above- and below-ground and the buffering of soil, the driving factors in leaf and root would show seasonal dynamic. We measured timing of above- and below-ground intensity in alpine steppe over non-growing season and growing season. Air temperature, precipitation, soil moisture and soil temperature were used to analyze the correlation based on the growth rhythm. An earlier growth in spring and a delay dormancy of root than leaf was observed. Our results strongly suggest that the soil moisture play a more important in leaf unfolding while temperature consistent to the withered of shoot. Soil moisture comes from soil melt driving the spring phenology of root, which derived from the storage of subsoil layer in last autumn. Climate change will affect the strong seasonal patterns that characterize these precipitation-limited systems, especially in the spring and fall shoulder seasons. As seasonality changes in the alpine steppe, divergent responses of leaf and fine root would be explored.